The Role of Transcranial Magnetic Stimulation in Inducing Neuroplasticity in Post-Stroke Rehabilitation (Research, Society and Development, 2023)
Introduction: Structural changes at the cellular level impact functional changes in the brain as a result of connections between the multiple networks responsible for the functions of the Central Nervous System. Stroke modifies the pattern of functional connectivity of brain regions, resulting in deficits intrinsic to the role now played by lost neurons. Objective: to understand, from the literature, the therapeutic implications of Transcranial Magnetic Stimulation in patients suffering from stroke. Methodology: this is a narrative review of the literature. Results and discussion: Ischemia in regions of the primary motor cortex results in an asymmetry between the cerebral hemispheres, characterized by increased recruitment and an abnormal reduction of cortical inhibition in the primary motor cortex contralateral to the injured hemisphere. This asymmetry in interhemispheric inhibition produces disparity in rehabilitation performance. Consequently, the recovery is centrally limited. Stimulation of the contralesional primary motor cortex and cerebellum improves muscle spasticity and limb dyskinesia. Repetition stimulation has demonstrated important usefulness in the treatment of post-stroke aphasia concomitant with speech therapy. Among changes in mental status, depression is the most common. Final considerations: The conditions secondary to the neuronal deficit caused by a stroke affect multiple dimensions of the patient's life. It is a safe, non-invasive strategy that produces good results. It is a promising device whose relevance should not be ignored or neglected.